EFEITO DO TRATAMENTO ÁCIDO EM MEIO AQUOSO E ALCOÓLICO NA MODIFICAÇÃO DO AMIDO DE PINHÃO (Araucaria angustifolia) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
Araucaria angustifolia (Bert.) O. Kuntze is a conifer present in Brazilian forests and its seeds are high in starch. The pinhões used in this research were derived from genetic material and selected based on preliminary tests because they presented a gelatinization temperature below the 60 ºC. This is considered an interesting and advantageous feature, which can save time and energy during the starch gelatinization process. Starch in its natural form has limitations, so one of the alternatives is acid hydrolysis, which has the purpose of altering its physicochemical properties. This treatment combined with alcoholic solution has the ability to recover majority of the granule. The aim of this study was to identify the effects of acidic modification on aqueous and alcoholic solutions of pinhão starches (A. angustifolia) with gelatinization temperatures below of 60 ºC. The samples were evaluated for pH and Colorimetry by thermal analysis (TG-DTA e DSC), by rheological behavior (RVA), by structural analysis (XRD and SEM) and by statistical analysis (ANOVA and Tukey). The recovery of the starch granule was higher in the aqueous medium and in the alcoholic solution; the values were close to 90% recovery. The pH values showed that the process eliminated the acid used in the modification and the Colorimetry identified the white and slightly yellow coloration for both accessions, showing that the treatments did not alter the colorimetric characteristics of the pinhão starches. In the TG-DTA curves in synthetic air, three mass losses were observed. The native samples presented a difference in the DTA and the final temperatures showed a higher thermal resistance of the starches. In the TG-DTA curves in nitrogen, two mass losses were found. The treated samples showed similarity in DTA and the final temperatures were not changed due to the inert atmosphere. In the DSC analysis, Tc and ΔHgel did not show significant differences, only in To and Tp. The most intense treatments showed light thermal resistance and lower ΔHgel. In the RVA, a reduction in the viscosity parameters was observed according to the intensity of the treatment. XRD identified the type C pattern for starches and relative crystallinity increased as the acid hydrolysis rate increased. Superficial changes in the granules were observed by SEM. Considering the results found, the pinhão starches demonstrated to be promising for industrial applications aiming specialties, that is, for products with reduced scale. The intention is to stimulate small producers, provide benefits to the final product and the maintenance of the species A. angustifolia.
Keywords: amido modificado; modificação ácida aquosa e alcoólica; TG-DTA; DSC; RVA; DRX; MEV; modified starch; aqueous and alcoholic acid modification; TG-DTA; DSC; RVA; XRD; SEM; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS